Eksplorasi Nilai Filosofis Kearifan Lokal sebagai Sumber Belajar IPS yang Inklusif - Febri Puja Rahayu,; Sudrajat, (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study systematically identifies and analyzes the philosophical values embedded within the Merti Rogo Tradition in Umbul Cokro, Klaten, by examining its ontological, epistemological, and axiological dimensions. Utilizing a comprehensive literature review methodology, this research synthesizes existing scholarly works to explore the tradition's profound potential as a contextual learning resource for Social Sciences (IPS). The primary aim is to understand how these identified values can be effectively internalized to cultivate positive character traits and mitigate bullying behaviors among students. Findings consistently indicate that the Merti Rogo Tradition embodies a holistic worldview, unique knowledge transmission methods, and fundamental ethical values such as togetherness, tolerance, and mutual respect. These insights are highly relevant for enriching IPS curriculum, strengthening students' cultural identity, and fostering an inclusive and supportive school environment. The study concludes that leveraging the philosophical depth of the Merti Rogo Tradition offers a meaningful cultural approach, providing a valuable framework for comprehensive character development and effective bullying prevention within educational settings.